If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -5n = 14 + -8n Solving 5 + -5n = 14 + -8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '8n' to each side of the equation. 5 + -5n + 8n = 14 + -8n + 8n Combine like terms: -5n + 8n = 3n 5 + 3n = 14 + -8n + 8n Combine like terms: -8n + 8n = 0 5 + 3n = 14 + 0 5 + 3n = 14 Add '-5' to each side of the equation. 5 + -5 + 3n = 14 + -5 Combine like terms: 5 + -5 = 0 0 + 3n = 14 + -5 3n = 14 + -5 Combine like terms: 14 + -5 = 9 3n = 9 Divide each side by '3'. n = 3 Simplifying n = 3
| 9-3x=2x-11 | | 2c-12=-2c | | 2x-3x=x | | x+(5+x)+(9+x)=59 | | X^2+2x+29=0 | | 23=k-0.7 | | 2x+6=16-3x | | 7b+11=11+7b | | x^2+27x+177=0 | | b+2.5=1 | | 3y+2x=21 | | 2(8h)=16(6h) | | x^2-6x+27=0 | | 22x^2-1=0 | | 4d+8d=1-27 | | Y=-5(2x-3) | | =0+10-8+2 | | 4p/7=7-9+6 | | 3a+7=4 | | 5x-11-4x+24=5 | | u-9=4u+15 | | 16x^6+8x^6=0 | | y=x^2-4x-60 | | 10-2n=3n-20 | | m(n)=m+n | | -6v=-12b | | 29=33.3+7 | | 0=ln(2x+5)*ln(9x^2) | | 8-2n-14=-27-9n | | 1.8x=0.9 | | -27=8+7x | | 45s=121 |